Learning Spanish sayings in the Spanish as a foreign language class - Fernández, Leyshack Sánchez (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Teachers are aware of the importance of using idioms, proverbs and slang intertwined in grammar lessons in order to make students to lear language and culture at the same time. The main goal is to achieve natural interaction, by the writing or the speaking, between students and native Spanish speakers. When students are able to write or speak in a natural and authentic way they proof that they understand not only the grammar but the culture and the habits of Spanish speakers. To reach this goal sayings must be included in the learning process as Spanish native speakers use them frequently in the day to day communication, in literature and in the media. This paper is a proposal to develop some activities focused in the usage of sayings in the E.L.E. (Spanish as a Foreign Language) classroom. Teachers of foreing language usually complain about the lack of time in the class to carry on cultural topics. For this reason we have designed the activities of this paper as complementary material for the language course. These activities are short, specific, entertaining and easy to include in the class routine. The practise of idioms, proverbs and slang must not be only part of the vocabulary learning as they help students to put into practise gramar structures and cultural knowledge.